2018
DOI: 10.1158/0008-5472.can-17-1752
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the ISG15-Specific Deubiquitinase USP18 as an Antineoplastic Target

Abstract: Ubiquitination and ubiquitin-like posttranslational modifications (PTM) regulate activity and stability of oncoproteins and tumor suppressors. This implicates PTMs as antineoplastic targets. One way to alter PTMs is to inhibit activity of deubiquitinases (DUB) that remove ubiquitin or ubiquitin-like proteins from substrate proteins. Roles of DUBs in carcinogenesis have been intensively studied, yet few inhibitors exist. Prior work provides a basis for the ubiquitin-specific protease 18 (USP18) as an antineopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…Furthermore, the relationship between USP18 DNA hypomethylated and USP18 RNA ac 4 C hyperacetylated in SLE should be explored in the future. It has been reported that engineered gain of USP18 decreases cancer growth by destabilizing growth-regulatory proteins ( Mustachio et al, 2018 ), which suggests that USP18 may alter transcribed mRNA catabolic process and translational initiation to facilitate the pathogenesis of SLE. In contrast, a previous study has discovered that the engineered loss of USP18 increases ISGylation ( François-Newton et al, 2011 ); therefore, upregulated USP18 might reduce ISGylation to inactivate the interferon response, implying the function of ac 4 C modification in SLE which should be identified in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relationship between USP18 DNA hypomethylated and USP18 RNA ac 4 C hyperacetylated in SLE should be explored in the future. It has been reported that engineered gain of USP18 decreases cancer growth by destabilizing growth-regulatory proteins ( Mustachio et al, 2018 ), which suggests that USP18 may alter transcribed mRNA catabolic process and translational initiation to facilitate the pathogenesis of SLE. In contrast, a previous study has discovered that the engineered loss of USP18 increases ISGylation ( François-Newton et al, 2011 ); therefore, upregulated USP18 might reduce ISGylation to inactivate the interferon response, implying the function of ac 4 C modification in SLE which should be identified in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study highlighted the requirement to target negative regulators like the ISGs, SOCS1 and SOCS3 and identified a natural compound 6-hydroxy-3- O -methyl-kaempferol 6- O -glucopyranoside (K6G) which inhibited SOCS3 expression and stimulated type I IFN induced ISRE reporter expression ( 138 ). There is also strong evidence that USP18 is worth pursuing as a promising target and recent advances in solving its crystal structure along with ISG15 should help make this idea a reality in the clinic ( 139 ). On the other hand, an IRF inhibitor, LY294002, which targets IFN-β production via IRF3 inhibition ( 140 ), has been shown to sensitize cancer cells to chemotherapy in cervical cancer cells by enhancing mitochondrial JNK signaling.…”
Section: Targeting Type I Ifn Signaling Pathway As a Promising Stratementioning
confidence: 99%
“…ISGylation is reversible through the deconjugating activity of USP18 [52] , [53] . USP18 transcripts were not increased in mt BRCA1 samples at baseline and emerged as significantly elevated only after FF exposure, when HERC5 transcripts were also elevated.…”
Section: Discussionmentioning
confidence: 99%